PENGARUH MUTU ASUHAN PERSALINAN NORMAL TERHADAP KOMPLIKASI PERSALINAN DI RUANG BERSALIN RSUD PROF DR.W.Z. JOHANNES KUPANG - SUNDARI, SUNDARI (MIDWIFERY MEDICAL JOURNAL, 2014)
Background: The results of the post-training evaluation to 88 midwives at the health center and health center (sub) in Kupang in APN showed competent 57 people (64.78%), not competent 31 people (35.22%). Midwives working in hospitals Prof. Delivery Room DR. WZ Johannes Kupang has never done training evaluations APN. Results Wati 2012, APN quality Midwife Hospital Prof. Dr. WZJohanesKupang still lacking / needs improvement 27 (90%). The number of midwives in the delivery room 32 midwives with diploma IV 6, Diploma 26 people. All have training APN. Total deliveries in 2013 as many as 1834 people, normal delivery midwife helped 945 people (51.5%) and there were 889 deliveries with the actions of people (48.5%). Deliveries with complications that extends the latent phase of 116 people (8.5%), the extension of the active phase of 107 people (7.8%), the extension of the second stage 114 people (7.9%) and fetal distress 102 people (7.5 %); Bleeding 18 people (1.2%); rupture of the perineum 427 people (45.2%). Not all midwives do APN evenly and continuously. Objective: To determine the influence of the quality of a normal delivery care for complications of childbirth.Hypothesis: There is a significant relationship between quality of Normal Delivery Care for complications of childbirth in Space Maternity Hospital Prof. Dr. WZ Johannes Kupang. Method: This was an observational analytic study with cross sectional design. The sample used in this study were 32 midwives in the delivery room. The data analysis is descriptive and inductive using linear regression analysis. Results: The value of the quality of regression koefiensi APN 0,001 compared with 0,005 less significant level means there is significant relationship between the quality of APN with delivery complications. Conclusion: There was a significant influence on the quality APN childbirth complications, especially rupture of the perineum and birth asphyxia.